2022
DOI: 10.1039/d2py00649a
|View full text |Cite
|
Sign up to set email alerts
|

Protected amine-functional initiators for the synthesis of α-amine homo- and heterotelechelic poly(2-ethyl-2-oxazoline)s

Abstract: Polymers bearing amine moieties are highly valuable for their ability to conjugate and/or complex a variety of molecules. However, their incorporation into synthetic macromolecules remains challenging. Poly(2-oxazolines) (POx) are a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Deprotection of phthalimide functionality on polymer ends was done as previously described. 62 Deprotection was achieved via hydrazinolysis with 50 mol excess hydrazine to the polymer at 120 °C, and subsequent purification with basic workup, precipitation into ether, and dialysis in 1 kDa membrane against MQ were achieved without consequential deprotection of dioxolane aldehyde protecting groups.…”
Section: Synthesis Of Polymersmentioning
confidence: 99%
“…Deprotection of phthalimide functionality on polymer ends was done as previously described. 62 Deprotection was achieved via hydrazinolysis with 50 mol excess hydrazine to the polymer at 120 °C, and subsequent purification with basic workup, precipitation into ether, and dialysis in 1 kDa membrane against MQ were achieved without consequential deprotection of dioxolane aldehyde protecting groups.…”
Section: Synthesis Of Polymersmentioning
confidence: 99%
“…[ 36 ] The cROP of (2‐oxazolines) proceeds with higher functional group tolerance, which has permitted the synthesis of PMOXa from initiators bearing alkyne groups [ 33 ] or protected thiols [ 37 ] and amines. [ 38 ]…”
Section: Polymer Synthesismentioning
confidence: 99%
“…[36] The cROP of (2-oxazolines) proceeds with higher functional group tolerance, which has permitted the synthesis of PMOXa from initiators bearing alkyne groups [33] or protected thiols [37] and amines. [38] Hydroxyl groups are not strictly "clickable", but nevertheless are used in many coupling reactions, as they are chemically stable and can readily be obtained from quenching, e.g. by the treat-ment of active chain-ends in cROP with basic water.…”
Section: Polymer Conjugationmentioning
confidence: 99%
“…Recently, our group reported that N -acylated poly­(aminoester) (NPAE)-based comb polymers with pendant carboxylic acid groups allow efficient functionalization with amine-functionalized compounds, including macromolecules, which offer a possibility of different structure formation and attachment of drugs and targeting ligands. Another class of polymers with a versatile range of available derivatives and end-group and side-chain functionalization , that offer great potential in biomedical applications because of their water solubility, biocompatibility, antifouling, and stealth effect are poly­(2-oxazoline)­s (POx). , The attachment of telechelic and multifunctional POx to NPAE-based comb polymers allows for incorporation of low-fouling moieties and the adjustment of their size and aspect ratio in a single step. Previously, it was reported that NPAE-based comb polymers showed cellular uptake through passive diffusion of cell membranes followed by efficient targeting of mitochondria with no negative effect to the cells in a mouse embryo fibroblast cell line (NIH/3T3) and a rat dopaminergic neural cell line (N27).…”
Section: Introductionmentioning
confidence: 99%